FAKTOR-FAKTOR YANG MEMPENGARUHI HUTANG JANGKA PENDEK, HUTANG JANGKA PANJANG DAN TOTAL HUTANG (Studi Kasus pada Perusahaan-perusahaan Manufaktur yang Terdaftar di BEI Selama Tahun 2007-2011) - Indra Wahyu Pradana; Tarmizi Achmad (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the impact of firm’s characteristics such as profitability, fixed asset, firm size, growth, earning volatility, and firm’s financial distress to short term debt, long term debt and total debt, simultaneously and partially. This study uses pecking order theory as the basic theory. The short term debt and long term debt are chosen as the dependent variable as it’s being a development of the former research which has much focused on the total debt only.By using the purposive sampling method, samples of 745 firms are selected due to its consistency of publishing financial reporting on the BEI. The data is analyzed using classical assumption test and hypothesizes are analyzed using the multiple linear regression model.The result of this study shows that profitability, fixed asset and financial distress variables have a significant impact to short term debt, long term debt, and firm’s total debt, but for the fixed asset variable, the significant effect affect on the different directionality as predicted. On the other side, firm’s size and earning volatility have a significant impact to long term debt and total debt but insignificant to short term debt. The last variable, growth, is found that it has significant impact to short term debt and total debt but insignificant to long term debt.